The Quality imperative (New York : McGraw Hill Education, 1994)
This primer presents current developments in the field of quality management. It gives readers an inside look at: quality in manufacturing, quality in service, quality in Japan and Europe, and quality strategies. It also profiles select firms that have won the Baldrige Award.
1. Questing for the best -- 2. The roots of quality: a short history -- 3. The global picture: how America stacks up with Japan and Europe -- 4. Quality's long, hard road -- 5. How to achieve quality: a guide to winning techniques -- 6. Chasing the dream: quality prizes and gurus -- 7. Quality in manufacturing -- 8. Quality in services -- 9. Quality in the public sector -- 10. Quality in R&D -- 11. TQM in the twenty-first century: paradigms for postmodern managers
Includes index.
Keywords: QUALITY OF PRODUCTS